2022
DOI: 10.30880/ijie.2022.14.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Severity Level Types and Trends in Road Accident Cases at Johor Inter State Road Using Analythical Hierarchy Process (AHP) And Geographical Information System

Abstract: Road traffic accidents are usually happened and keep increasing year by year in Malaysia. It will give a adverse impact at the road also to the road user. There are several causes that contribute to the accident such as faulty vehicle, uneven roads, driverbehavior and many more. So, with all these causes, it might be the reason why the road accidents keep on increasing. The purpose of this case study is to determine the highest road accident ranking based on the types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…They compared AHP with the forced ranking method in terms of a pairwise comparison of crash factors and found that the AHP performed better in representing the importance of factors with in-depth details. Saifullizan et al (2022) [19] used the AHP method to rank and weigh car crashes according to the different categories of injury using data from Balai Traffic Batu Pahat Johor, Malaysia, from October 2016 to October 2020. They prioritized wreckage injuries at the top of the hierarchy system, followed by fatal injuries, minor injuries, and serious injuries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared AHP with the forced ranking method in terms of a pairwise comparison of crash factors and found that the AHP performed better in representing the importance of factors with in-depth details. Saifullizan et al (2022) [19] used the AHP method to rank and weigh car crashes according to the different categories of injury using data from Balai Traffic Batu Pahat Johor, Malaysia, from October 2016 to October 2020. They prioritized wreckage injuries at the top of the hierarchy system, followed by fatal injuries, minor injuries, and serious injuries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Traditional AHP is one of the methods more frequently used in traffic crash analysis to methodically assess the seriousness and significance of factors involved in traffic crashes. It uses pairwise comparisons and determines the relative importance of various variables, including the state of the roads, driving habits, vehicle features, and environmental factors [17][18][19]. The traditional AHP methods, however, do not consider the actual occurrence or practical impact of each criterion when making a choice, which can produce biased results [27].…”
Section: Budapest Hungarymentioning
confidence: 99%
“…Thus, 1AT contains only seven different classes to be predicted, which are significantly fewer than 3AT, consisting of 297 different accident types to be predicted [10]. Furthermore, other research on building classifiers based on police accident data often focuses on predicting or modelling injury-related parameters, for example, the accident severity or the number of injured people [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], or investigating risk factors [30], [31], [32], [33], [34], [35], [36]. Additionally, models regarding crash type, typically describing how road users hit each other, 1 seem to be part of the research focus [37], [38], [39], [40], [41].…”
Section: Introductionmentioning
confidence: 99%